Strategi penghimpunan dana zakat profesi pada pegawai swasta di Baitul Mal Aceh Tamiang - mudia Ayumi; Muslem; mutia Sumarni (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2022)
Objectives – This study aims (1) to determine the strategy in collecting professional zakat funds carried out by Baitul Mal Aceh Tamiang, (2) to determine the implementation of professional zakat fund collection carried out by Baitul Mal Aceh Tamiang Method – The type of research used in this study was descriptive qualitative with a normative-juridical approach, with data collection techniques namely observation, interviews and documentation. Research Results – The results of this study indicate that: (1) the strategy of Baitul Mal Aceh Tamiang in collecting professional zakat funds for private employees in their environment has been carried out properly, namely by providing zakat education for proppective muzzaki (persons who pay zakat), (2) implementation carried out by Baitul Mal, namely by forming a special zakat collection unit for private employees to make it easier for muzakki to pay their zakat obligations. Limitations – This study has limitations in terms of the relatively small number of research subjects, then the research subjects are people who consistently pay professional zakat. Practical Implications – As a practical implication, the results of this study can be used as a reference by the government, especially zakat institutions in encouraging professional zakat fund collection strategies that are in accordance with the behavior of the community in paying professional zakat.